Peran Penggunaan Bahasa Indonesia dalam Meningkatkan Daya Tarik dan Minat Konsumen Lokal di Era Pemasaran Digital - Syairal Fahmy; Simon Herbeth Saragih; Tasya Chintain; Rizky Nur Ramadhan; Susilo Susilo; Ricce Sukmawati; Lenny Kartika (CV. ULIL ALBAB CORP, 2024)
The proper and accurate use of the Indonesian language in digital marketing content plays an important role in increasing consumer appeal and interest. This study shows that using Indonesian that is easy to understand, informative, and engaging can strengthen communication between marketers and consumers, while reducing the potential for misunderstandings. Consumers generally prefer marketing content that uses Indonesian over foreign languages, due to its relevance to everyday contexts and ease of comprehension. Furthermore, the creative use of Indonesian, combining elements of local wisdom and current trends, can enhance the competitiveness of products in the market. However, the research also reveals that marketing content presented in a slang words format tends to be easier to attract the attention of consumers. Therefore, an effective digital marketing strategy must prioritize the creative use of Indonesian as the primary means of interacting with the target market, especially in the context of the local market.